Silent hypoxaemia in COVID‐19 patients. (4th January 2021) - Simonson, Tatum S.; Baker, Tracy L.; Banzett, Robert B.; Bishop, Tammie; Dempsey, Jerome A.; Feldman, Jack L.; Guyenet, Patrice G.; Hodson, Emma J.; Mitchell, Gordon S.; Moya, Esteban A.; Nokes, Brandon T.; Orr, Jeremy E.; et al.
Abstract: The clinical presentation of COVID‐19 due to infection with SARS‐CoV‐2 is highly variable with the majority of patients having mild symptoms while others develop severe respiratory failure. The reason for this variability is unclear but is in critical need of investigation. Some COVID‐19 patients have been labelled with 'happy hypoxia', in which patient complaints of dyspnoea and observable signs of respiratory distress are reported to be absent. Based on ongoing debate, we highlight key respiratory and neurological components that could underlie variation in the presentation of silent hypoxaemia and define priorities for subsequent investigation. Abstract : Abstract figure legend Genesis of air hunger. In a working model of mechanisms giving rise to air hunger, brainstem respiratory centres send projections (corollary discharge) to the forebrain, giving rise to breathing discomfort in proportion to the magnitude of corollary discharge (Banzett et al ., 2021 in press ). These brainstem respiratory centres also send descending projections, driving respiratory motor neurons and respiratory muscle activity to generate ventilation. Inputs to the brainstem centres include chemoreceptor inputs, exercise and voluntary inputs from the motor cortex. Afferent feedback from lung stretch receptors modulates different qualities of dyspnoeic sensation. Slowly adapting lung stretch receptors are inhibitory to air hunger. Pulmonary C‐fibre receptors contribute to air hunger, but precise neural projections are not well understood. Whenever corollary discharge reaches a certain threshold, or when ventilation fails to meet demand, dyspnoea ensues. Inputs contributing to dyspnoea are indicated by blue arrows; inputs that inhibit dyspnoea are indicated with blue circles. Black arrows indicate homeostatic regulation of breathing.